Perdamaian atau Keadilan? Transformasi untuk Perempuan di Wilayah Konflik dan Pascakonflik di Papua dan Aceh - Sri Lestari Wahyuningroem (Yayasan Jurnal Perempuan, 2021)
In conflict or post-conflict contexts, women experience layered violence: both daily and structural. The two main approaches commonly used in studies and programs in both contexts are peace and transitional justice. Both give a focus on violence experienced by women, but are not sufficient to provide analysis and solutions to the occurrence of structural injustice experienced by women. This paper is a reflection of the long journey of the author’s involvement in both approaches. The main question of this paper is: how can peace and transitional justice provide solutions to transform structural injustices experienced by women in conflict and post-conflict areas? Where to start?